Comparing the effectiveness of attachment-based play therapy and parent-child relationship therapy on the psychological well-being of children with separation anxiety disorder - Mahsa Najmi; Reza Ghorban Jahromi; Esmail Sadipour; Mansoureh Karimzadeh (مجله علوم روانشناختی, 2024)
Background: According to the World Health Organization, 20% of children and adolescents worldwide currently have mental health problems, but effective treatment coverage in this area is very low. Therefore, the application of evidence-based interventions for children with separation anxiety disorder is a fundamental necessity. Aims: This study aimed to compare the effectiveness of play attachment therapy and play therapy based on the parent-child relationship on the psychological well-being of children with separation anxiety disorder. Methods: The method of the present study is quasi-experimental and a pre-test, post-test-follow-up design of 2 months was used to collect data. The statistical population of this study included all mothers and children aged five to six years old with separation anxiety who were enrolled in preschool centers or kindergartens in District 4 of Tehran in the academic year 2022-2023. An experimental group and a control group were assigned. The experimental groups received attachment-focused play therapy for 8 sessions of 90 minutes and play therapy based on parent-child relationships for 10 sessions of 120 minutes. To collect data, a psychological well-being questionnaire (Abed et al., 2016) was used. Data were analyzed using SPSS.24 software using repeated measure analysis of variance. Results: The results of repeated measure analysis of variance showed that each Attachment-based play therapy and parent-child relationship play therapy significantly improved the psychological well-being of children with separation anxiety disorder (P< 0.05). The results of Bonferroni's post hoc tests showed that there was no difference between Attachment-based play therapy and parent-child relationship play therapy in the post-test and follow-up stages. Conclusion: According to the above, and the relatively high prevalence of this disorder and its comorbidity with other disorders among children and adolescents, the use of evidence-based interventions such as Attachment-based play therapy and parent-child relationship play therapy can significantly reduce their psychological distress.